Consumption of Mixed Fruit-juice Drink and Vitamin C Reduces Postprandial Stress Induced by a High Fat Meal in Healthy Overweight Subjects - Peluso, Ilaria; V. Villano, Debora; A. Roberts, Susan; Cesqui, Eleonora; Raguzzini, Anna; Borges, Gina; Crozier, Alan; Catasta, Giovina; Toti, Elisabetta; Serafini, Mauro (Current Pharmaceutical Design, 2014)
Postprandial stress induced by acute consumption of meals with a high fat content results in an increase of markers of cardiometabolic risk. Repeated acute dietary stress may induce a persistent low-grade inflammation, playing a role in the pathogenesis of functional gut diseases. This may cause an impairment of the complex immune response of the gastrointestinal mucosa, which results in a breakdown of oral tolerance. We investigated the effect of ingestion of a fruit-juice drink (FJD) composed by multiple fruit juice and extracts, green tea extracts and vitamin C on postprandial stress induced by a High Fat Meal (HFM) in healthy overweight subjects. Following a double blind, placebo controlled, cross-over design, 15 healthy overweight subjects were randomized to a HFM providing 1334 Kcal (55% fat, 30% carbohydrates and 15% proteins) in combination with 500 mL of a placebo drink (HFM-P) or a fruit-juice drink (HFM-FJD). Ingestion of HFM-P led to an increase in circulating levels of cholesterol, triglycerides, glucose, insulin, TNF-α and IL-6. Ingestion of HFM-FJD significantly reduced plasma levels of cholesterol and triglycerides, decreasing inflammatory response mediated by TNF-α and IL-6. Ingestion of a fruit-juice drink reduce markers of postprandial stress induced by a HFM.
Keywords: postprandial stress